Compressive strength of efficient self‐compacting concrete with rice husk ash, fly ash, and calcium carbide waste additives using multiple artificial intelligence methods. (30th October 2021) - Mustafa Mohamed, Abdeliazim; Osman Bashir, Maaz; Dirar, Samir; Beshir Osman, Nisreen
Abstract: The principal benefit of mixed concrete is to minimize the disadvantages of certain complementary cement ingredients by combining them with other better materials so that overall costs are managed and efficiencies of concrete production are increased. The structural and economic characteristics of concrete can also be improved. In this work, the compressive strength (CS) of self‐compacting concrete (SCC) was assessed and their interrelations were addressed using binary and ternary cementitious combinations of rice husk, fly ash (FA), and calcium carbide. Accordingly, various admixtures were prepared with diverse amounts of wastes by substituting ordinary Portland cement (5%). Thus, due to the raising of rice husk and FA, the CS of SCC was considerably improved. To raise the accuracy of the analysis, three soft computing models of particle swarm optimization (PSO), adaptive neuro‐fuzzy inference system (ANFIS), and artificial neural network (ANN) were used. Six input parameters comprising FA replacement ratio, rice husk, total cementitious material, water cement ratio, high ratio water reducing agent and age of samples (AS), and one output parameter as the CS of SCC have been investigated. Subsequently, following the root mean square error and R 2 results, three methods were shown as reliable tools for assessing the influence of cementitious material on CS of self‐compact concrete; however, ANFIS remarkably was better than ANN and PSO. As a result, rice husk showed less contribution to the strength of concrete at short times, but much at longer time than FA and calcium carbide. The enhanced influence of low amount of calcium carbide on CS was not significant. Also, it was found that the specimen incorporating of cement with 15% calcium carbide showed better workability than that of normal SCC specimen without calcium. Therefore, rice husk ash showed higher potential to be applied as partial replacements in SCC production.